Effect of Communication, Competency and Job Stress on Employee Performance at Atmindo - Hendry; Vanessa Hiustar; Viny Stevanie; Jessica Yendy; Jasmine (Journal of Research in Business, Economics, and Education, 2021)
The purpose of this study is to analyze the decline in employee performance at PT Atmindo Tbk. HR plays an important role in achieving the goals of an organization or company. Therefore, human resources are required to be professional and efficient in facing the challenges and opportunities that exist. The validity test is used with a population of 100 people and 35 people from companies engaged in the same industry. The method used is quantitative with quantitative descriptive research, using interviews, distributing questionnaires and documentation study. Multiple liner regression, coefficient of determination and simultaneous testing that will be used in the analysis method. It can be concluded that communication, competence and work stress simultaneously and partially have a positive effect on employee performance.